Steering self-organisation through confinement. Issue 9 (13th February 2023) - Araújo, Nuno A. M.; Janssen, Liesbeth M. C.; Barois, Thomas; Boffetta, Guido; Cohen, Itai; Corbetta, Alessandro; Dauchot, Olivier; Dijkstra, Marjolein; Durham, William M.; Dussutour, Audrey; Garnier, Simon; Gelderblom, Hanneke; et al.
Abstract : In this perspective article, we discuss how soft matter can spearhead efforts to harness confinement as a tool to steer self-organisation across different scales and disciplines. Abstract : Self-organisation is the spontaneous emergence of spatio-temporal structures and patterns from the interaction of smaller individual units. Examples are found across many scales in very different systems and scientific disciplines, from physics, materials science and robotics to biology, geophysics and astronomy. Recent research has highlighted how self-organisation can be both mediated and controlled by confinement. Confinement is an action over a system that limits its units' translational and rotational degrees of freedom, thus also influencing the system's phase space probability density; it can function as either a catalyst or inhibitor of self-organisation. Confinement can then become a means to actively steer the emergence or suppression of collective phenomena in space and time. Here, to provide a common framework and perspective for future research, we examine the role of confinement in the self-organisation of soft-matter systems and identify overarching scientific challenges that need to be addressed to harness its full scientific and technological potential in soft matter and related fields. By drawing analogies with other disciplines, this framework will accelerate a common deeper understanding of self-organisation and trigger the development of innovative strategies to steer it using confinement, with impact on, e.g., the design of smarter materials, tissue engineering for biomedicine and in guiding active matter.